Perception of Electrical Engineering Students in Aceh towards the Application of Artificial Intelligence in the Digital Era - Sadrina, Sadrina; Mustapha, Ramlee; Fathurrahman, Fathurrahman; Putri, Gina Saria (DPTE FT UNY, 2024)
The goal of artificial intelligence is to build robots that can learn, reason, and adapt to carry out complicated tasks. The research aims to provide essential guidance to enhance students' knowledge related to artificial intelligence devices. The highlights of the need for Indonesian engineering students to align their competencies with the 4.0 industrial revolution by developing knowledge in adopting artificial intelligence to improve Indonesia's technological standing in fields such as power electronics. The respondent of the study involved 125 electrical engineering students in Aceh. The questionnaire is the chosen instrument aimed at obtaining perceptions from electrical engineering students regarding their knowledge of artificial intelligence devices. The research revealed that electrical engineering students in Aceh struggle with understanding artificial intelligence applications due to limited exposure, a lack of expert guidance, unfamiliarity with programming elements, and insufficient explanation of AI concepts in their curriculum.